Mg and Zn co-doped mesoporous ZSM-5 as an ideal catalyst for ethane dehydroaromatization reaction. Issue 23 (28th September 2022) - Sumi, Tomoka; Kokuryo, Shinya; Fujimoto, Yugo; Li, Xinyu; Miyake, Koji; Uchida, Yoshiaki; Nishiyama, Norikazu
Abstract : Mg and Zn co-doped mesoporous ZSM-5 was prepared via impregnation of Mg and a Zn ion exchange using a commercial ZSM-5, which achieved a high yield of BTX and the improvement of catalyst lifetime on EDA reaction. Abstract : Ethane dehydroaromatization (EDA) is a promising method for synthesizing benzene, toluene, and xylene (BTX) to meet the increasing demand for these compounds. Zn 2+ -ion exchanged MFI-type zeolite (ZnZSM-5) is an active catalyst for EDA reactions. However, ZnZSM-5 is rapidly deactivated by coke formation due to its excess acidity derived from aluminum (Al) sites. In this study, we prepared Mg and Zn co-doped ZSM-5 zeolites for EDA reactions. Mg species were loaded in the ZSM-5 zeolites using an impregnation method, whereas Zn species were introduced via an ion exchange process. By optimizing the synthesis conditions, Mg- and Zn co-doped ZSM-5 zeolites demonstrated unique properties: (1) high content of Zn species with moderate dehydrogenation activity, (2) mesoporosity, and (3) mild acidity, all of which contributed to higher BTX yields and a longer catalyst lifetime in the EDA reaction compared to those in the EDA reactions with ZnZSM-5 as the catalyst. This work contributes to the progress of catalyst design for transforming light alkanes into value-added chemicals.